An Insight Into Systemic Immune Response in Leishmania donovani Mediated Atypical Cutaneous Leishmaniasis in the New Endemic State of Himachal Pradesh, India - Thakur, Lovlesh; Madaan, Priyanka; Jain, Aklank; Shankar, Vinay; Negi, Ajeet; Chauhan, Shashi Bhushan; Sundar, Shyam; Singh, Om Prakash; Jain, Manju (Frontiers in Immunology, 2022)
Leishmaniasis continues to afflict in known and newer endemic sites despite global efforts towards its control and elimination. In this regard, emergence of newer endemic sites with unusual disease format is recognized wherein Leishmania donovani complex classically known to cause visceral disease is demonstrated to cause cutaneous manifestation. In this context atypical cutaneous leishmaniasis (CL) cases caused by L. donovani genetic variants from the newer endemic state of Himachal Pradesh (HP) in India, are beginning to be understood in terms of parasite determinants. The atypical CL manifestation further needs to be explored to define host immune-correlates with possible role in driving the unusual disease progression. In the given study, we performed a comprehensive systemic-immune profiling of the atypical cutaneous leishmaniasis patients from the study area in HP, India, in comparison to the classical visceral leishmaniasis (VL) patients from the northeast region of India. The systemic immune response was studied using ELISA-based assessment of Th1, Th2, Th17, Treg, Th22 specific plasma cytokine expression pattern, and parasite-specific total serum IgG/IgG subclasses. The specified immune-correlates are known to exhibit heterogeneous association with the different infecting parasite species, infection load, and co-lateral host immunopathology in classical CL and VL. In the atypical CL patient group, altered expression of IL-10 emerged as the key finding that could potentially fine-tune the Th1/Th17/Th22 effector cytokine axis towards a localized cutaneous manifestation. A reduced expression of IL-10 along with a high IFN- γ /IL-10 ratio as a read-out of effective parasite killing defined atypical cutaneous outcome. In contrast, a high circulatory IL-10 levels and a depressed IFN- γ /IL-10 ratio was seen in classical VL patients in line with an ineffective parasite-killing cytokine response. Overall, the study highlights new knowledge on host immune-correlates in terms of cytokine expression pattern and IgG subclasses that underline atypical disease manifestation such that L. donovani, a generally visceralizing parasite species cause skin localized cutaneous lesions.